2017
DOI: 10.1039/c7dt03153j
|View full text |Cite
|
Sign up to set email alerts
|

μ-Pyridine-bridged copper complex with robust proton-reducing ability

Abstract: The binuclear copper complex [Cu(DQPD)]2 (where DQPD = deprotonated N,N-di(quinolin-8-yl)pyridine-2,6-dicarboxamide (DQPDH2)) was synthesised and characterised by various spectroscopic as well as electrochemical techniques. The binuclear copper complex was converted into a mononuclear one by the addition of 2 equivalents of pTsOH into [Cu(DQPD)]2. The interconversion between the dimer and monomer complex was studied through UV-Vis spectroscopy and cyclic voltammetry. The mononuclear copper complex showed high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 68 publications
0
25
0
Order By: Relevance
“…333 In contrast, Cu 2 3 gave a TON H2 of 2135 over 20 h in H 2 O:DMF (1:4) with TEA and PS8 using visible LED light. 341 While Cu 2 3 was stable over 12 h under irradiation in H 2 O:DMF (1:4), reactivation of photocatalysis after 22 h required addition of HEC, rather than PS. 341…”
Section: Homogeneous Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…333 In contrast, Cu 2 3 gave a TON H2 of 2135 over 20 h in H 2 O:DMF (1:4) with TEA and PS8 using visible LED light. 341 While Cu 2 3 was stable over 12 h under irradiation in H 2 O:DMF (1:4), reactivation of photocatalysis after 22 h required addition of HEC, rather than PS. 341…”
Section: Homogeneous Catalysismentioning
confidence: 99%
“…341 While Cu 2 3 was stable over 12 h under irradiation in H 2 O:DMF (1:4), reactivation of photocatalysis after 22 h required addition of HEC, rather than PS. 341…”
Section: Homogeneous Catalysismentioning
confidence: 99%
“…of TsOH to give a monocopper species that catalyzed proton reduction. 20 The dicobalt unit in 1 is more robust than its copper counterpart, indicating the structure is likely retained throughout the catalytic process. In it notable that 4 equiv.…”
Section: Electrocatalytic Studies Of the Dinuclear Complexesmentioning
confidence: 99%
“…5,8 However, recent studies have shown that ligand-assisted and ligand-centered mechanistic pathways significantly improve the kinetics and lower the overpotential of the HER by obviating the need the generate an electron rich Co ion. [15][16][17] In such mechanisms, the protonation occurs at the ligand, [18][19][20][21] and the protons subsequently interact with a metal-hydride to release H 2 . Furthermore, it has been shown that redox non-innocent ligands participate in the H 2 evolution pathways of various metal complexes, by contributing both protons and electrons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation